2020
DOI: 10.1002/eap.2058
|View full text |Cite
|
Sign up to set email alerts
|

Comparing abundance distributions and range maps in spatial conservation planning for migratory species

Abstract: Most spatial conservation planning for wide‐ranging or migratory species is constrained by poor knowledge of species’ spatiotemporal dynamics and is only based on static species’ ranges. However, species have substantial variation in abundance across their range and migratory species have important spatiotemporal population dynamics. With growing ecological data and advancing analytics, both of these can be estimated and incorporated into spatial conservation planning. However, there is limited information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 62 publications
2
33
0
Order By: Relevance
“…Some species, for example, Marsh Harriers ( Circus aeruginosus , Vardanis et al 2011), may visit different sites when moving between consistently used breeding and non‐breeding locations across multiple migrations, whereas others, for example, Hudsonian Godwits ( Limosa haemastica , Senner et al 2014), use the same stopover sites each year. Understanding the ways in which species consistently use some sites and sporadically use others not only provides meaningful insights into migration ecology for instance, ontogeny of migratory patterns (Mueller et al 2013, Verhoeven et al 2018) and intraspecific variation in migratory patterns (Battley et al 2012, Senner 2012), but such information also has value for implementing effective conservation actions (Martin et al 2007, Runge et al 2015, Reynolds et al 2017, Johnston et al 2019).…”
mentioning
confidence: 99%
“…Some species, for example, Marsh Harriers ( Circus aeruginosus , Vardanis et al 2011), may visit different sites when moving between consistently used breeding and non‐breeding locations across multiple migrations, whereas others, for example, Hudsonian Godwits ( Limosa haemastica , Senner et al 2014), use the same stopover sites each year. Understanding the ways in which species consistently use some sites and sporadically use others not only provides meaningful insights into migration ecology for instance, ontogeny of migratory patterns (Mueller et al 2013, Verhoeven et al 2018) and intraspecific variation in migratory patterns (Battley et al 2012, Senner 2012), but such information also has value for implementing effective conservation actions (Martin et al 2007, Runge et al 2015, Reynolds et al 2017, Johnston et al 2019).…”
mentioning
confidence: 99%
“…Alternatively, natural disturbances can increase the overall habitat needed to support viable populations (Allison et al., 2003). Highly mobile species pose additional challenges for conservation planners, because their natural intra‐ and inter‐annual movements also require consideration (Gilmore et al., 2007; Johnston et al., 2020; Runge et al., 2014; Schuster et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat suitability modeling that considers the dynamic trends of species distributions improved habitat prioritization for conservation planning [64]. We found that considering temporally specific environmental drivers also produced different results from the model that used long-term averages as predictor variables.…”
Section: Species Conservationmentioning
confidence: 89%